Labour Market Model - Focused on Final Products (Advances in Systems Science and Applications, 2015)
This paper studied history of development of commodity and cash flows balancing models. Keynesian model , monetary model and Mundell-Fleming model are investigated, the issues of mutual consistency of indicators of economic growth is studied. At the same time, the mathematical formulation of market equilibrium of levels of production, employment, incomes and prices is gives. A new model of labour market focusing economy on the final product is established.